PENGARUH GAYA KEPEMIMPINAN DAN IKLIM ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN - Rahadian, Made Agastia; Suwandana, I Gusti Made (E-Jurnal Manajemen; Vol 6 No 6 (2017), 2017)
ABSTRACT   This study was conducted to determine the effect of leadership styleand organizational climate on job satisfaction at PDAM Tirta Mangutama Badung. The study was conducted on employees PDAM Tirta Mangutama Badung by the number of respondents as many as 52 employees. The number of respondents is determined using saturation sampling technique. The data collection is done by distributing questionnaires using a 5-point Likert scale to measure 18 indicators. Data analysis technique used is multiple linear regression. The test results leadership style positive and significant impact on job satisfaction and organizational climate positive and significant impact on job satisfaction. The limitation of this study is the location of this research will be in the scope of the PDAM Tirta Mangutama Badung so the results of this study can not explain the circumstances of the other besides PDAM Tirta Mangutama Badung. Keywords :leadership style, organizational climate, job satisfaction
Keywords: leadership style, organizational climate, job satisfaction